Translation strategies of cultural words in Tarian Bumi novel and its translation - Robingah, Robingah; Ali, Ahmad Jum'a Khatib Nur (CV. Mitra Palupi, 2021)
Background: Translation is an activity of changing one language into target language. There are a lot of problems encounter by the translator in translating text such as problem in translating poetry, cultural items, idiomatic expression, literature text and many others. Tarian Bumi is an Indonesian novel written by Oke Rusmini where in the novel there are a lot of cultural words, cultural items, especially Balinese culture. Purpose: The purpose of this research article is first to find out the cultural categories of the cultural words found in Tarian Bumi novel and its translation. And second to analyze the translation strategies used by the translator in translating the cultural words found in Tarian Bumi novel and its translation.Design and methods: This research article applied qualitative methods and using documentation technique in collecting the data. In categorizing the cultural words, Newmark’s theory is applied. To find out the translation strategies used by the translator, the theory of Baker of translation strategies is used.Results: The cultural words found in Tarian Bumi novel and its translation are 58 data. From Newmark’s theory of cultural words category, there are 4 categories found, they are: ecology with 1 data, material culture with 14 data, social culture with 6 data, and organization, concept, ideas with 35 data. After the data are categorized based on the cultural category, then writer analyzed the translation strategies. The result is there are only 5 translation strategies found. The strategies found are: 1) translation by more general word 9 data, 2) translation by using cultural substitution 12 data, 3) translation by using loan word or loan word plus explanation 25 data, 4) descriptive equivalent 11 data, 5) translation by omission with only 1 data.